2020
DOI: 10.1002/pssb.201900707
|View full text |Cite
|
Sign up to set email alerts
|

Smart Honeycomb “Mechanical Metamaterials” with Tunable Poisson's Ratios

Abstract: Mechanical metamaterials represent a class of deformable systems, which exhibit macroscopic deformations, mechanical, and/or thermal properties. These emerge due to the structure of their subunits rather than their materials composition and typically exhibit anomalous (normally negative) macroscopic structural, mechanical, or thermal property/properties caused by a change in shape/size of the system. Herein, a class of honeycombs is discussed, which push to the extreme the classical definition of “mechanical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 98 publications
(138 reference statements)
0
17
0
Order By: Relevance
“…Having established that the concepts presented previously can be used to generate deformations which convert T‐shaped junctions to arrow (↑) or Y‐shaped junctions upon the application of temperature and/or pressure variations, it would be useful to discuss some of the potential applications that this concept may have. These include the construction of alternative designs, possibly even more versatile systems with tunable properties, particularly when bearing in mind that the re‐entrant version of these honeycombs (obtained through a change in temperature/pressure) is expected to be auxetic, whereas the non‐re‐entrant versions are expected to exhibit conventional Poisson's ratio behavior …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Having established that the concepts presented previously can be used to generate deformations which convert T‐shaped junctions to arrow (↑) or Y‐shaped junctions upon the application of temperature and/or pressure variations, it would be useful to discuss some of the potential applications that this concept may have. These include the construction of alternative designs, possibly even more versatile systems with tunable properties, particularly when bearing in mind that the re‐entrant version of these honeycombs (obtained through a change in temperature/pressure) is expected to be auxetic, whereas the non‐re‐entrant versions are expected to exhibit conventional Poisson's ratio behavior …”
Section: Resultsmentioning
confidence: 99%
“…These include the construction of alternative designs, possibly even more versatile systems with tunable properties, particularly when bearing in mind that the re-entrant version of these honeycombs (obtained through a change in temperature/pressure) is expected to be auxetic, whereas the non-re-entrant versions are expected to exhibit conventional Poisson's ratio behavior. [59] For example, it is possible to construct other space filling models based on this concept of bimaterial strips. In particular, one may build systems which upon deformation resemble the starshaped space filling systems as exemplified by Grima et al [55] some of which are shown in Figure 14.…”
Section: Alternative Designs and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[25] In the last article of this section, 'Smart Honeycomb "Mechanical Metamaterials" with Tunable Poisson's Ratios', James N. Grima-Cornish et al show how the composite honeycombs having T-shaped junctions could be made to exhibit temperaturedependent Poisson's ratios. [26] This time the section other systems with "negative" characteristics is represented by three papers. The first of them, 'On the Design of Multimaterial Honeycombs and Structures with T-Shaped Joints Having Tunable Thermal and Compressibility Properties' by Reuben Cauchi et al, shows that the composite honeycombs having T-shaped junctions, which were also the subject of the last paper of the previous section, can exhibit negative thermal expansion and/or negative compressibility, the magnitude of which could be fine-tuned though design.…”
mentioning
confidence: 99%